Does it pay to say "I do"? Marriage bonuses and penalties across the EU - Michael Christl; Silvia De Poli; Viginta Ivaškaitė-Tamošiūnė (Global Labor Organization (GLO), 2021)
We analyse the different fiscal treatment of married and cohabiting couples across all EU Member States using microsimulation methods. Our paper highlights important differences across EU countries' tax-benefit systems, where seven countries show substantial bonuses for married couples and four exhibit marriage penalties. On a micro level, we find that these marriage bonuses/penalties differ substantially across household types and income. From a policy point of view, our results suggest that the abolishment of marriage-related tax-benefit components in countries with marriage bonuses would leave some households financially worse off but would increase governments revenues that could be spent to targeted support of specific groups. From both an equity and a gender equality point of view, this abolishment would be desirable.
Keywords: H31; J12; J18; 330; marriage; cohabitation; marriage penalty; inequality; tax-benefit systems; Europe